Effect of magnesium addition on the vacancy-Mg binding free enthalpy in Al-Cr alloys - Beatrice, Carlos Roberto Sobreira; Garlipp, Waldir; Cilense, Mário; Adorno, Antonio Tallarico (Eclética Química, 2002)
The Mg-vacancy binding free enthalpy of Al-Cr solid solution alloys with Mg addition was calculated by electrical resistivity measurements. The obtained value is lower than that obtained for dilute Al-Mg alloys with almost the same Mg content and may be attributed to the diffusion of Mg.